Co/Zn bimetallic oxides derived from metal organic frameworks for high performance electrochemical energy storage. (20th November 2018) - Lim, Gwendolyn J.H.; Liu, Ximeng; Guan, Cao; Wang, John
Abstract: Partial isomorphic substitution of Zinc in a two-dimensional Cobalt-based (Co-based) bimetallic Metal Organic Frameworks (MOFs) has been successfully synthesised on carbon cloth. Specifically, the Zn content corresponding to the Co to Zn ratio of 2:1 has been incorporated into the Co-based framework during the growth process. Cobalt-based bimetallic oxides ZnCo2 O4 are then derived: one from the Bimetal Organic Frameworks via oxidation in air, and the other by first annealing in N2 for stabilisation before oxidation. Systematic characterisation results, including those using XRD, SEM, EDS, TEM and XPS, support the effective incorporation of Zn into the Metal Organic Frameworks. The nanocrystalline bimetallic oxides derived from MOFs exhibit flake-like morphology, the size and thickness of which are affected by Zn addition. Electrochemical performance of the MOF-derived nanocrystalline bimetallic oxides assembled on carbon cloth was examined in a KOH electrolyte (3 M) as the electrolyte at room temperature. The bimetallic oxides show an improvement in specific capacity by more than 300% over that of MOF-derived Co3 O4 when used as an electrode material in supercapacitors, together with much improved stability. The capacity loss is reduced from 30.0% to less than 5.2% after 2000 charge–discharge cycles. This work illustrated the potential of bimetallic oxide structures derived from MOFs in delivering high supercapacitor performance.